COLLAGE 360: A Model of Person-Centered Care to Promote Health Among Older Adults - Elizabeth P. Howard; Robert Schreiber; John N Morris; Aline Russotto; Susan Flashner-Fineman (Journal Of Aging Research And Healthcare, 2016)
Health care leaders and providers have introduced the assumption the typical elder, even in the presence of complex, chronic disease and prevailing illness, is capable of assuming greater personal responsibility for their health care, with a shift from provider-centered to a person-centered model of care. For older adults who often face challenges managing and maintaining their health status, guidance and support is needed. In this project, COLLAGE 360, a comprehensive assessment system and wellness coaching program that focuses on prevention and wellness was implemented in one continuing care retirement community. Following completion of two assessment tools through directed conversations with a wellness coach, older adults developed an individualized vitality plan that outlined life goals, supporting goals and action plans for goal achievement. Results from this program suggest engagement in the assessment and wellness coaching process via the COLLAGE 360 program translated into sample older adults sensing that they live in a more supportive environment when compared with elders not receiving any wellness coaching. In addition, the older adults had positive responses in the areas of mood and life satisfaction. Strategies to improve health and well being need an extended focus beyond the older adult’s medical conditions and consider psychological, spiritual and social needs with personal preferences being paramount. These issues are foundational to a person-centered, health promotion approach needed among older adults.
Keywords: person-centered care